JUMPA Vol. 4 No. 1, Feb 2017 PENGARUH HARGA JUAL, KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP MINAT BELI BATIK JAMBI: PENGARUH HARGA JUAL, KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP MINAT BELI BATIK JAMBI - Effiyaldi STIKOM Dinamika Bangsa Jambi (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2017)
The lowbuying interestof society toBatikJambi is an issueraised inthis study. This study aimstomeasure how muchthe public interest Jambi Jambi batik dikukurof variables ; selling price, product quality andproduct design. The results show, that the variable selling price, product quality andproduct design are examined contained no significant effect on the public interest against the city of Jambi Jambi batik. Should be new break through sand benc markingandor cooperation withother regionsthat have been successfulin raising batik to the national market and international market, so find solutions for problems that occuraround Jambi batik.